2017
DOI: 10.1103/physreve.95.052316
|View full text |Cite
|
Sign up to set email alerts
|

Alliance formation with exclusion in the spatial public goods game

Abstract: Detecting defection and alarming partners about the possible danger could be essential to avoid being exploited. This act, however, may require a huge individual effort from those who take this job, hence such a strategy seems to be unfavorable. But structured populations can provide an opportunity where a largely unselfish excluder strategy can form an effective alliance with other cooperative strategies, hence they can sweep out defection. Interestingly, this alliance is functioning even at the extremely hig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(42 citation statements)
references
References 52 publications
0
39
0
Order By: Relevance
“…where k c gives the number of neighboring cooperators of a defector with k neighbors [20]. Note that h, t and g are constant parameters.…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…where k c gives the number of neighboring cooperators of a defector with k neighbors [20]. Note that h, t and g are constant parameters.…”
Section: Modelmentioning
confidence: 99%
“…Moreover, various studies have found empirical evidences of indirect pressure as a consequence of the ostracism mechanism [13,[15][16][17][18][19]. It is notable that ostracism is very similar to another mechanism known as social exclusion [20][21][22]. In social exclusion, freeriders are shunned and ignored, with the collective production gain and benefits of the community being excluded from the defectors.…”
Section: Introductionmentioning
confidence: 99%
“…Still, spatial prisoners dilemma with expellers can also be considered as a kind of coevolutionary model between individual strategies and network structures as the neighborhoods of individuals are also coevolved with strategies in our model [22]. Recently, the impact of social exclusion on the evolution of cooperation governed by group interaction has been extensively studied in infinite populations, finite populations and spatial networks, respectively [105][106][107]. In their works, excluders are able to deny the rights of defectors to enjoy the benefits of public goods at some cost.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…In particular, the public goods game has been recognized as a paradigm, which succinctly describes the essential dilemma of cooperation [2,6]. Recent works on the public goods game have proposed effective means to enable the evolution of cooperation, such as punishment [7][8][9][10][11][12][13], reward [14][15][16], exclusion [17][18][19][20], and individual migration [21].…”
Section: Introductionmentioning
confidence: 99%